A review of enabling factors in construction industry productivity in an Australian environment. Issue 2 (1st April 2014) - Hughes, Rami; Thorpe, David
Abstract : Purpose: – The purpose of the research discussed in this paper is to ascertain the perception, from the project manager's viewpoint, of factors affecting construction productivity in the State of Queensland, Australia. Design/methodology/approach: – The research was conducted by a structured questionnaire that was sent to 89 randomly selected construction project managers in Queensland, Australia. This questionnaire requested background information about the respondents and then sought a score, using a 0-4 Likert scale, from each of them with respect to the importance of 47 factors identified from the literature that were considered likely to affect construction productivity. The factors were stratified into primary factors and secondary factors contributing to three of the primary factors. There were 36 responses. These factors were rated by the respondents and then ranked using a relative importance index approach. Findings: – The research evaluated the relative importance of the primary factors with respect to their effect on construction productivity. The 15 highest ranking factors are discussed. Three factors – rework, poor supervisor competency, and incomplete drawings – were ranked as having a strong effect on construction productivity. There was also an analysis of the secondary factors in relation to three of the primary factors. Research limitations/implications: – The research focused on the State of Queensland in Australia. It had a response rate of 40 per cent. It provides insight into the factors affecting productivity on construction projects in Australia. Further research to investigate the identified factors in depth, using targeted interviews of expert project management professionals, is currently being undertaken. Practical implications: – The construction industry can use the findings in this paper as a basis for improving the productivity of construction projects. Originality/value: – This research is original research, which has highlighted a number of key areas of which construction productivity can be improved.